Prognostic value of systemic immune-inflammation index for colorectal cancer: a systematic review and meta-analysis - Wang, Pengfei; Jiang, Huiying (Frontiers in Oncology, 2026)
BackgroundAlthough the systemic immune-inflammation index (SII) has gained attention as a prognostic biomarker in colorectal cancer (CRC), existing studies report inconsistent findings due to methodological variability. This meta-analysis was conducted to clarify the prognostic value of SII in CRC.MethodsPubMed, Embase, the Cochrane Library and Web of Science were systematically searched for literature up to November 2025. The association between SII and clinical outcomes in CRC was identified. Studies that satisfying the inclusion and exclusion criteria were selected. Progression-free survival (PFS) and overall survival (OS) were the primary outcomes, which were presented by hazard ratios (HRs) with 95% confidence intervals (CIs). Heterogeneity and the stability of results were performed by subgroup and sensitivity analyses. Review Manager 5.4 and STATA 15.1 were conducted to analyze.ResultsThirty-five studies with 26812 cases were included. Elevated SII was associated with poorer OS (HR = 2.11, 95% CI: 1.73–2.57, p < 0.00001) and PFS significantly (HR = 2.16, 95% CI: 1.83–2.54, p < 0.00001). These associations remained consistent across subgroups stratified by geographic region, treatment modality, TNM stage, tumor location, and sample size. Sensitivity analyses confirmed the stability of the results. No significant publication bias exists for OS (p = 0.669) or PFS (p = 0.261) through Egger’s test.ConclusionElevated pre-treatment SII is associated with unfavorable survival and disease progression in CRC. However, the retrospective design of included studies and the substantial heterogeneity in SII cut-off values underscore the need for large-scale, prospective, multicenter investigations with standardized methodologies to validate these findings and establish optimal threshold values for clinical application.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251010606.